Sodium-glucose cotransporter-2 inhibitors and risk for genitourinary infections in older adults with type 2 diabetes - Navya Varshney; Sarah J. Billups; Joseph J. Saseen; Cy W. Fixen (SAGE Publishing, 2021)
Background and aims: Although landmark clinical trials have demonstrated an increased risk for genitourinary infection (GUI) after initiation of sodium-glucose cotransporter-2 inhibitor (SGLT2i) therapy that led to an FDA label warning, real world findings have been inconsistent and evidence specifically in older adults is lacking. The objective of the study was to examine the incidence of GUI in patients aged 65 years or older initiated on SGLT2i compared with glucagon-like peptide-1 receptor agonist (GLP1-RA) therapy at a large academic health system. Methods: A retrospective population-based cohort study was conducted using electronic health records of patients aged 65 years and older with a diagnosis of type 2 diabetes mellitus. Patients newly initiated on SGLT2i or GLP1-RA therapy with estimated glomerular filtration rate (eGFR) ⩾30 mL/min per 1.73 m² and active within the health system for at least 1 year prior to initiation were included. We compared the incidence of inpatient, emergency room, or outpatient diagnosis of GUI (bacterial and mycotic) within 6 months of SGLT2i or GLP1-RA initiation. A chi-square or Fisher's exact test were used to analyze between-group differences for categorical variables, while a t -test was used for continuous variables. A Cox proportional hazards model was used to estimate the impact of confounding variables on the primary outcome. Results: One hundred and thirty-three patients were initiated on SGLT2i therapy and 341 patients newly initiated on GLP1-RA therapy. After adjusting for differences in age, A1c, body mass index, eGFR, race and sex, there was no statistically significant difference in GUI incidence within 6 months of SGLT2i versus GLP1-RA initiation (3.8% versus 6.5%, adjusted hazard ratio: 0.784, 95% confidence interval 0.260-2.367). Conclusion: We found no increased risk of composite GUI within 6 months of initiating SGLT2i compared with GLP1-RA therapy. These real-world data in older adults add to previous findings, which suggest no increased risk of urinary tract infection with SGLT2i initiation. Plain language summary A class of antidiabetic medications and risk for genitourinary infections in older adults with type 2 diabetes Older adults with type 2 diabetes often benefit from a class of antidiabetic medications known as sodium-glucose cotransporter-2 inhibitors (SGLT2is) which help to lower blood glucose, decrease risk for cardiovascular disease and prevent kidney disease progression. However, there is concern that these medications may increase risk for urinary tract infections and/or genital fungal infections in older adults based on clinical trial evidence. Our study evaluated the real-world occurrence of these safety events in patients aged 65 years or older who were newly started on these medications. We compared these patients with a group of patients newly started on an alternative class of antidiabetic agents which are not expected to increase risk for infections, known as glucagon-like peptide-1 receptor agonists (GLP1-RA). In our study, we included 133 patients who started an SGLT2i and 341 patients who started a GLP1-RA at a large teaching hospital. We evaluated the occurrence of infection up to 6 months after initiation of these mediations. We found no significant difference in infection rate between these two groups. We conclude in the study that the use of SGLT2i in older adults was not associated with increased risk for urinary tract infections or genital fungal infections when compared with GLP1-RA use.